Condiciones ergonómicas y salud ocupacional de los albañiles en la construcción de la marina turística en Iquitos, Loreto 2024 - Lopez Valdivia, Blanca Fernanda (2024)
The thesis evaluates the ergonomic conditions and occupational health of construction workers at the tourist marina in Iquitos, where uncomfortable postures and a lack of ergonomic tools contribute to cumulative fatigue and physical discomfort. Through surveys, direct observation, and the REBA method, risks associated with physical exertion and sustained postures were identified. Although workers perceive their environment as safe, physical demands impact their well-being, particularly in the back, hands, and legs. The results suggest the need to implement ergonomic training, redesign tools, and establish active breaks. These measures could reduce health risks, improve productivity, and promote a safer, healthier work environment.